Composition of Hawthorn (Crataegus spp.) Fruits and Leaves and emblic Leafflower (Phyllanthus emblica) Fruits - Liu, Pengzhan (fi=Turun yliopisto|en=University of Turku|, 2012)
Hawthorn (Crataegus sp.) is widely distributed in the northern hemisphere (Asia, Europe and North America). It has been used as a medicinal material and food for hundreds of years both in Europe and in China. Clinical investigations and other research suggest that extracts of hawthorn fruits and leaves have multiple health effects including hypolipidaemic, anti-atherosclerotic, hypotensive, cardioprotective and blood vessel relaxing activities. Hawthorn fruit extracts have also displayed antioxidant and radical scavenging activities. Emblic leafflower fruit (Phyllanthus emblica) is widely used in Chinese and Indian traditional medicine. It has been found to have anti-cancer, hypoglycaemic and hypolipidaemic activities as well as cardioprotective effects and antioxidant activity. The fruit is currently used as a functional food targeted at obese people in China. Phenolic compounds, procyanidins (PCs), flavonols and C-glycosyl flavones in hawthorn and hydrolysable tannins in emblic leafflower fruits are considered among the major bioactive compounds in these berries. Moreover, hawthorn and emblic leafflower fruits are rich in vitamin C, triterpenoids, fruit acids, sugar alcohols and some other components with beneficial effects on the health of human beings. The aim of the thesis work was to characterise the major phenolic compounds in hawthorn fruits and leaves and emblic leafflower fruits as well as other components contributing to the nutritional profile and sensory properties of hawthorn fruits. Differences in the content and compositional profile of the major phenolic compounds, sugars, acids and sugar alcohols within various origins and species of hawthorn were also investigated. Acids, sugars and sugar alcohols in the fruits of different origins/cultivars belonging to three species (C. pinnatifida, C. brettschneideri and C. scabrifolia) of hawthorn were analysed by gas chromatography (GC-FID) and mass spectrometry (Publication I). Citric acid, quinic acid, malic acid, fructose, glucose, sorbitol and myo-inositol were found in all the subspecies. Sucrose was present only in C. scabrifolia and three cultivars of C. pinnatifida var. major. Forty-two phenolic compounds were identified/tentatively identified in fruits of C. pinnatifida var. major by polyamide column chromatography combined with high-performance liquid chromatograph-electrospray ionisation mass spectrometry (HPLC-ESI-MS) (Publication II). Ideain, chlorogenic acid, procyanidin (PC) B2, (-)-epicatechin, hyperoside and isoquercitrin were the major phenolic components identified. In addition, 35 phenolic compounds were tentatively identified based on UV and mass spectra. Eleven major phenolic compounds (hyperoside, isoquercitrin, chlorogenic acid, ideain, (-)-epicatechin, two PC dimers, three PC trimers and a PC dimer-hexoside) were quantified in the fruits of 22 cultivars/origins of three species of Chinese hawthorn by HPLC-ESI-MS with single ion recording function (SIR) (Publication III). The fruits of the hawthorn cultivars/origins investigated fell into two groups, one rich in sugars and flavonols, the other rich in acids and procyanidins. Based on the compositional features, different biological activities and sensory properties may be expected between cultivars/origins of the two groups. The results suggest that the contents of phenolic compounds, acids, sugars and sugar alcohols may be used as chemotaxonomic information distinguishing the hawthorn species from each other. Phenolic compounds in fruits and leaves of C. grayana and their changes during fruit ripening/harvesting were investigated using HPLC-UV-ESI-MS (Publication IV). (-)-Epicatechin, PC B2 and C1, hyperoside and a quercetin-pentoside were the major phenolic compounds in both fruits and leaves. Three C-glycosyl flavones (a luteolin-C-hexoside, a methyl luteolin-C-hexoside and an apigenin-C-hexoside) were present in leaves in abundance, but only at trace levels in fruits. Ideain and 5-O-caffeoylquinic acid were found in fruits only. Additionally, eleven phenolic compounds were identified/tentatively identified in both leaves and fruits (three B-type PC trimers, two B-type PC tetramers, a quercetin-rhamnosylhexoside, a quercetin-pentoside, a methoxykaempferol-methylpentosylhexoside, a quercetin-hexoside acetate, a methoxykaempferol-pentoside, chlorogenic acid and an unknown hydroxycinnamic acid derivative). The total content of phenolic compounds reached the highest level by the end of August in fruits and by the end of September in leaves. The compositional profiles of phenolic compounds in fruits and leaves of C. grayana were different from those of C. pinnatifida, C. brettschneideri, C. scabrifolia, C. pinnatifida. var. major, C. monogyna, C. laevigata and C. pentagyna. Phenolic compounds in emblic leafflower fruits were characterised by Sephadex LH-20 column chromatography combined with HPLC-ESI-MS (Publication V). A mucic acid gallate, three isomers of mucic acid lactone gallate, a galloylglucose, gallic acid, a digalloylglucose, putranjivain A, a galloyl-HHDP-glucose, elaeocarpusin and chebulagic acid represented the major phenolic compounds in fruits of emblic leafflower. In conclusion, results of this study significantly increase the current knowledge on the key bioactive and nutritional components of hawthorn and emblic leafflower fruits. These results provide important information for research on the mechanism responsible for the health benefits of these fruits.